HUBUNGAN BEBAN KERJA DENGAN KELELAHAN KERJA PADA PETUGAS SAMPAH DI DINAS LINGKUNGAN HIDUP KOTA MASOHI PROVINSI MALUKU - Alfiyanti Linda Lewenussa; Arief Fardiansyah; Mukhammad Himawan Saputra (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2022)
Excessive workloads cause fatigue for waste officers, by improving workloads it can reduce waste officer fatigue and increase work productivity. The purpose of the study was to identify the workload of waste officers, identify work fatigue of waste officers and analyze the relationship between workload and work fatigue of waste officers at the environmental service of Masohi City, Maluku Province. This study used a cross sectional research design. The sample used as many as 36 respondents garbage officers. Sampling using simple random sampling technique. The instruments used are workload observation sheets and work fatigue questionnaire sheets, stationery, digital cameras. Data analysis was performed using the Spearman rank test. The results of this study indicate that some of the workloads experience light workloads with results of 94,14%. Fatigue shows that some experience moderate work fatigue with a result of 63.9%. Statistical test results obtained p value = 0.004 with a correlation value = 0.471 which means there is a relationship. It can be concluded that there is a significant relationship between workload and work fatigue and the strength of the relationship is sufficient or strong enough for the waste officer at the environmental service office, Masohi city, Maluku province. Suggestions that can be given to the relevant agencies are to take advantage of the best possible rest time to minimize the occurrence of fatigue.